Effects of Computer-Assisted Working Memory Training Programme on Working Memory Ability and Mathematical Performance of Children at Risk of Mathematical Learning Difficulties - Kamyar Azimi; Manijeh Shehniyailagh; Alireza Hajiyakhchali; Maneli Shehni Karamzadeh (پژوهش‌های علوم شناختی و رفتاری)
Working memory is an important domain-general cognitive that can impair the ability to remember and use mathematical concepts and procedures in children at risk of mathematical learning difficulties. The purpose of this study was to investigate the effect of a computer-assisted working memory training programme on the working memory ability and mathematical performance of children at risk of mathematical learning difficulties. The research method utilized in this study was a field experiment with a pre-test, post-test, and follow-up design with a control group. The participants were 30 first-grade children from 12 elementary schools in Kuhdasht City, who were randomly assigned to an experimental group (n = 15) and a control group (n = 15). Children were assessed using a variety of measures, including the Number Sense Brief Screener, Number Knowledge Test, Raven's Colored Progressive Matrices Test, Child Symptom Inventory, and Working Memory Index of the Wechsler Intelligence Scale for Children (WISC-V), and Number Sets Test. The computer-assisted working memory training programme was conducted three times a week for six weeks. Results showed a significant improvement in both working memory (p = .002) and mathematical performance (p = .0001) of the control group compared to the control group in post-test and follow-up phase. Findings show that working memory training can enhance working memory in children at risk of mathematical learning difficulties (near transfer) and help optimize these children's mathematical performance potential (far transfer).IntroductionResearch has demonstrated the academic benefits of working memory training in typically developing preschool and kindergarten children (Honore & Noel, 2017), those with attention and working memory deficits (Bergman-Nutley & Klingberg, 2014), and children with math dyscalculia in the later years of elementary school (Layes et al., 2018). However, the benefits of implementing cognitive intervention programs, including working memory training, for first-grade children at risk of mathematical learning difficulties are still unclear. So far, only one study has investigated this issue internationally (Munez et al., 2022). Additionally, very few empirical studies include follow-up evaluations. Most importantly, it is uncertain whether the positive effects observed in laboratory settings can be replicated in real-world learning environments. Therefore, the present study aimed to determine the effects of near and far transfer of working memory training on working memory ability and mathematical performance of children at risk of mathematical learning difficulties in the first grade of elementary school in an educational setting. MethodThe current study is a field experiment utilizing a pre-test, post-test, and follow-up design with a control group. The participants were 30 first-grade children from 12 elementary schools in Kuhdasht city, who were randomly assigned to an experimental group (n = 15) and a control group (n = 15). Children were assessed using a variety of measures, including the Number Sense Brief Screener (Jordan et al., 2010), Number Knowledge Test (Griffin, 2010), Raven's Colored Progressive Matrices Test (Raven et al., 1998), Child Symptom Inventory (Gadow & Sprafkin, 1994), Working Memory Index of the Wechsler Intelligence Scale for Children (WISC-V, Groth-Marnat & Wright, 2016), and Number Sets Test (Geary et al., 2009). The computer-assisted working memory training programme was conducted three times a week for six weeks. Data were analyzed using AMOS (version 24) and SPSS (version 26) programs. FindingsThe descriptive data for the control and the experimental groups is discussed. In Table 1 the descriptive data for the experimental group and the control group for all measures on the pre-, post-, and follow- up tests are presented. At the pre-test, there were significant differences on visual working memory and mathematical performance between the groups in favor of the control group.Table 1. Means and standard deviations of the test scores on the pre-, post-, and follow-up tests for the experimental group (n = 15) and the control group (n = 15) Experimental groupControl groupMSDMSDPre-test    Working memory19.874.4820.673.14Mathematical performance3.301.013.410.83Post-test    Working memory28.093.5023.523.15Mathematical performance5.040.853.631.21Follow-test    Working memory26.193.9023.053.47Mathematical performance4.871.043.480.94 The MANCOVA results indicated that the experimental and control groups differed significantly in at least one of the dependent variables. This conclusion is based on the findings from the Wilks' Lambda test conducted during both the post-test (F(2,25) = 7.89, p = .002) and follow-up (F(2,25) = 18.62, p = .0001) stages. To determine this difference, an ANCOVA within a MANCOVA was conducted on the post-test and follow-up scores of the dependent variables. The results showed that the F values of the ANCOVA for working memory ability and mathematical performance in both the post-test (F(1.26) = 12.06, p = ./002, F(1.26) = 7.84, p = .009) and follow-up phases (F(1.26) = 25.09, p = .0001, F(1.26) = 9.81, p = .004) were statistically significant. Discussion and ConclusionThe results indicated that after adjusting for pre-test scores, a group of children who underwent working memory training, experienced a significant increase in their working memory abilities (near transfer effects) and mathematical performance (far transfer effects) compared to the control group. This improvement was observed in both the post-test and follow-up assessments. These encouraging findings are consistent with previous research on children with typical development, low socioeconomic status, and disabilities (Honore & Noel, 2017; Munez et al., 2022). The limitations of this study include a relatively small sample size and the use of an inactive control group. Researchers should consider examining and replicating the results of this study with a larger sample size across various schools, potentially nationwide, and including an active control group. In summary, the computer-assisted working memory training programme can effectively improve the working memory abilities and mathematical performance of children at risk of mathematical learning difficulties in school and classroom settings.